A qualitative exploration of feedback experience among final-year physiotherapy students using activity theory - Alison Lupton-Smith; Nicoline Herman; Anna Schmutz (BMC Medical Education)
Abstract Background Feedback is an important part of learning, however, it often does not have the desired effect. Much work has been done exploring students’ engagement with feedback and factors which may impact engagement. Mutual understanding of feedback and feedback practice on the part of the student and educator is essential. Methods This study explored the perceptions of feedback of final-year physiotherapy students at Stellenbosch University (South Africa). Twelve semi-structured interviews were conducted to generate data. Cultural-historical activity theory was used as an analytic lens in the data analysis. Results Students understood feedback to be a continuous, bidirectional conversation in which they were actively involved. Students recognised their agency in feedback practice. Despite their understanding, their agency was often undermined by factors such as the environment, context and most notably the perceived positioning and relationships between students and educators. Educators who were perceived as credible and created a safe psychosocial space had a positive influence on the students’ perception of feedback. Conclusions Students’ perceptions of feedback and their engagement was the product of a complex and dynamic interplay of factors. While students recognise their agency, this may be hindered by relationships and the design of feedback in the curriculum. As educators, one must consider how we contribute to this and enable students to activate and use their agency in feedback practice.